Pengembangan Sistem Informasi Penjualan Berbasis Website Untuk Usaha Kerajinan Kayu Jati di Kabupaten Ngawi - Chavindro Bunga Mardiasto; Achmad Arwan; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Abstract The rapid development of technology has made most people create new ideas in utilizing technology. The sales information system is the result of innovation in the use of rapidly growing technology. The sales information system is an electronic platform for marketing products through the internet that brings together sellers and buyers with courage. In the face of competition in the era of globalization, website-based sales information systems provide great opportunities for IKM players in Ngawi Regency to convey product information using technology connected to the internet. Selection of a website-based platform with the aim of facilitating the transaction process between craft entrepreneurs and buyers because information about handicraft products is available in the website-based sales information system catalog and can be accessed 24 hours every day. The development of this sales information system uses the waterfall method which has stages including other requirements, design, implementation, testing, and application and maintenance. This system produces 43 functional requirements and 4 actors from the results of the needs analysis that has been carried out. The sales information system in the implementation stage uses the Codeigniter framework and uses the programming languages ​​PHP, HTML, and CSS. Tests carried out in the study used two methods, namely the white box testing method for conducting unit testing and the black box method for validating testing. The results of the test process using the white box method are 100% valid from the 3 tested functionalities, while the results of the test process with the black box method are 100% valid from the 43 tested functionalities.